Problems of Development of Social Partnership in the Field of Labor and Protection of Labor Rights of Employees - A. I. Rashidova; L. A. Rashidova (Теоретическая и прикладная юриспруденция)
The article deals with the actual problem of the effectiveness of the national model of social partnership in the labor sphere in modern conditions of political, social and economic development. Based on domestic practice, the article emphasizes the importance of social partnership in ensuring a balance of interests of hired workers, entrepreneurs and the government in favor of society as a whole. The authors analyze the key features of the mechanism of social partnership in countries with developed market economies, highlighting the priority of using peaceful methods in resolving social conflicts, the participation of representatives of employees in production management. The article reveals the reasons for the insufficient effectiveness of social partnership in Russia and suggests ways to improve it, emphasizing the need to intensify the participation of all stakeholders in developing decent working conditions, reducing unemployment and poverty, and increasing the competitiveness of the economy. The article also notes the weakness of the trade union movement and the insufficient equality of partners in the field of social and labor relations, suggesting ways to improve this situation and activate social partnership as a key tool for ensuring social justice and economic development. The authors emphasize the importance of social partnership as an integral element of social and labor relations and as a key factor of social stability and economic progress.